Altered Colonic Bacterial Fermentation as a Potential Pathophysiological Factor in Irritable Bowel Syndrome. (September 2015) - Ringel‐Kulka, Tamar; Choi, Chang Hwan; Temas, Daniel; Kim, Ari; Maier, Daniele M; Scott, Karen; Galanko, Joseph A; Ringel, Yehuda
Abstract : OBJECTIVES: Dysbiosis leading to abnormal intestinal fermentation has been suggested as a possible etiological mechanism in irritable bowel syndrome (IBS). We aimed to investigate the location and magnitude of altered intestinal bacterial fermentation in IBS and its clinical subtypes. METHODS: IBS patients who satisfied the Rome III criteria (114) and 33 healthy controls (HC) were investigated. Intestinal fermentation was assessed using two surrogate measures: intestinal intraluminal pH and fecal short‐chain fatty acids (SCFAs). Intraluminal pH and intestinal transit times were measured in the small and large bowel using a wireless motility capsule (SmartPill) in 47 IBS and 10 HC. Fecal SCFAs including acetate, propionate, butyrate, and lactate were analyzed by capillary gas chromatography in all enrolled subjects. Correlations between intestinal pH, fecal SCFAs, intestinal transit time, and IBS symptom scores were analyzed. RESULTS: Colonic intraluminal pH levels were significantly lower in IBS patients compared with HC (total colonic pH, 6.8 for IBS vs. 7.3 for HC, P =0.042). There were no differences in total and segmental pH levels in the small bowel between IBS patients and HC (6.8 vs. 6.8, P =not significant). The intraluminal colonic pH differences were consistent in all IBS subtypes. Total SCFA level was significantly lower in C‐IBS patients than in D‐IBS and M‐IBS patients and HC. The total SCFA level in all IBS subjects was similar with that of HC. Colonic pH levels correlated positively with colon transit time (CTT) and IBS symptoms severity. Total fecal SCFAs levels correlated negatively with CTT and positively with stool frequency. CONCLUSIONS: Colonic intraluminal pH is decreased, suggesting higher colonic fermentation, in IBS patients compared with HC. Fecal SCFAs are not a sensitive marker to estimate intraluminal bacterial fermentation.